The relationships between HCAHPS communication and discharge satisfaction items and hospital readmissions - Fadi Hachem; Jeff Canar; Francis Fullam; Andrew Gallan; Samuel Hohmann; Catherine Johnson (The Beryl Institute, 2014)
The Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey has become a key metric used by organizations and patients to evaluate patient experience. Readmissions also continue to be a metric used to evaluate performance because of the added cost to both healthcare systems and patients. Both measures are also seen in programs such as Value Based Purchasing that have an effect on hospital reimbursements. Previous studies have demonstrated a relationship between patient perceptions and quality of care, and have found patients to be reliable evaluators of their care. While good communication and positive provider relationships have been related to higher satisfaction and higher rates of treatment compliance, past research has been limited to evaluating the relationship between readmissions and satisfaction at an organizational level. This retrospective, cross-sectional study will examine the relationship between communication and discharge HCAHPS questions and readmissions at 30 days, specifically at the patient level. Of the eight HCAHPS questions analyzed, higher scores on questions regarding "nurses listening" and "doctors explaining information" were linked to a decreased risk of readmission, while higher scores regarding "help after discharge" were linked to an increased risk for readmission. These results show the importance that a patient's severity of illness and hospital procedures have on explaining HCAHPS results. This study's seemingly paradoxical findings suggest the need to recognize potential trade-offs when reviewing HCAHPS results and using them to drive patient experience initiatives.